2000
DOI: 10.1002/(sici)1099-0518(20000101)38:1<60::aid-pola8>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Solvent effects on the free-radical copolymerization of styrene with butyl acrylate. I. Monomer reactivity ratios

Abstract: The free‐radical copolymerization of styrene with butyl acrylate was carried out in benzene and benzonitrile at 50°C. Differences between the apparent reactivity ratios determined in this work and those previously reported in bulk indicated noticeable solvent effects. This is explained by a qualitative bootstrap effect. © 2000 John Wiley & Sons, Inc. J Polym Sci A: Polym Chem 38: 60–67, 2000

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 33 publications
3
12
0
Order By: Relevance
“…The apparent reactivity ratios obtained with PA as cosurfactant in the reaction medium are differing from the values obtained with OA as cosurfactant under present study. The reactivity ratio of STY decreases whereas the reactivity ratio of the n ‐butyl acrylate increases while the polarity of the solvent in the reaction medium increases 44. A similar behavior was observed in STY/MMA copolymerization system when the copolymerization was performed in benzene, chlorobenzene, and benzonitrile; that is, the apparent reactivity ratio of STY diminished and the MMA reactivity ratio increased with the increase of solvent polarity 45.…”
Section: Resultssupporting
confidence: 57%
“…The apparent reactivity ratios obtained with PA as cosurfactant in the reaction medium are differing from the values obtained with OA as cosurfactant under present study. The reactivity ratio of STY decreases whereas the reactivity ratio of the n ‐butyl acrylate increases while the polarity of the solvent in the reaction medium increases 44. A similar behavior was observed in STY/MMA copolymerization system when the copolymerization was performed in benzene, chlorobenzene, and benzonitrile; that is, the apparent reactivity ratio of STY diminished and the MMA reactivity ratio increased with the increase of solvent polarity 45.…”
Section: Resultssupporting
confidence: 57%
“…This should be attributed to the different monomer activities of St and nBA. Thanks to its strong conjugate structures, styrene monomer has much higher reactivity than nBA, as evidenced by their reactivity ratio ( r nBA = 0.189, r St = 0.865, bulk at 50 °C) . It is well accepted that the midchain radicals have a very low reactivity so that they are more difficult to initiate a chain growth in the polymerization of butyl acrylate in this case .…”
Section: Resultsmentioning
confidence: 93%
“…Furthermore, there is experimental evidence24–28 that the bootstrap model, proposed by Harwood,6 is the most appealing as a general model. Harwood observed that copolymers with the same compositions have the same microstructure, which is independent of the solvent used during their preparation.…”
Section: Resultsmentioning
confidence: 99%